Apixaban: Alternative Anticoagulation for HeartMate 3 Ventricular Assist Device. Issue 3 (March 2022) - Whitehouse, Katherine R.; Avula, Divya; Kahlon, Tanvir; Costelle, Devan; Dunbar-Matos, Christina; Pahwa, Siddharth; Trivedi, Jaimin R.; Slaughter, Mark S.
Abstract : Patients with left ventricular assist devices currently require long-term anticoagulation with warfarin. Warfarin requires frequent blood tests and is associated with adverse events when not in the therapeutic range. Apixaban is a possible alternative that is potentially better for compliance and requires no additional testing. The purpose of this study was to compare adverse events in patients with a HeartMate 3 LVAD receiving apixaban versus warfarin. Thirty-five patients underwent HM3 implantation between January 01, 2016 to January 31, 2021. The groups compared were apixaban (n = 15, 43%) and warfarin (n = 20, 57%). All patients received 325 mg aspirin daily. Stroke, bleeding, and death were identified as primary outcomes after LVAD implant. Univariate nonparametric statistical analysis was performed. The median duration of treatment with apixaban was 148 days (37–606 days). The groups were comparable in terms of age (56 vs . 54 years), gender (male, 85% vs . 75%), and renal function (Cr 1.5 vs . 1.4). The apixaban group had significantly higher mean pulmonary artery pressure (41 vs . 34, p = 0.03) and there were more ( p < 0.05) ischemic cardiomyopathy and INTERMACS profile >3 in the warfarin group. At 6 months, thrombotic complications and death were not different between the groups. The two deaths in the apixaban group were from right heart failure. The apixaban group had clinically lower rates of bleeding complications (5% vs . 30%). The adverse events of bleeding, stroke, and death were similar in HM3 patients receiving warfarin or apixaban. Apixaban may be a safe alternative anticoagulant therapy in HM 3 LVAD patients.